Knowledge gaps and research recommendations for essential tremor. (December 2016) - Hopfner, Franziska; Haubenberger, Dietrich; Galpern, Wendy R.; Gwinn, Katrina; Van't Veer, Ashlee; White, Samantha; Bhatia, Kailash; Adler, Charles H.; Eidelberg, David; Ondo, William; Stebbins, Glenn T.; Tanner, Caroline M.; et al.
Abstract: Essential tremor (ET) is a common cause of significant disability, but its etiologies and pathogenesis are poorly understood. Research has been hampered by the variable definition of ET and by non-standardized research approaches. The National Institute of Neurological Disorders and Stroke (USA) invited experts in ET and related fields to discuss current knowledge, controversies, and gaps in our understanding of ET and to develop recommendations for future research. Discussion focused on phenomenology and phenotypes, therapies and clinical trials, pathophysiology, pathology, and genetics. Across all areas, the need for collaborative and coordinated research on a multinational level was expressed. Standardized data collection using common data elements for genetic, clinical, neurophysiological, and pathological studies was recommended. Large cohorts of patients should be studied prospectively to collect bio-samples, characterize the natural history of the clinical syndrome including patient-oriented outcomes, investigate potential etiologies of various phenotypes, and identify pathophysiological mechanisms. In particular, cellular and system-level mechanisms of tremor oscillations should be elucidated because they may yield effective therapeutic targets and biomarkers. A neuropathology consortium was recommended to standardize postmortem analysis and further characterize neuropathological observations in the cerebellum and elsewhere. Furthermore, genome-wide association studies on large patient cohorts (>10, 000 patients) may allow the identification of common genes contributing to risk, and whole exome or genome sequencing may enable the identification of genetic risk and causal mutations in cohorts and well-characterized families. Highlights: More collaborative and coordinated research across all disciplines is needed for future research in ET. Standardized data collection using common data elements are required. Very large cohorts of patients should be studied prospectively on a multinational level. Characterization of the natural history of the ET syndromes is needed. A neuropathology consortium should be formed and bio-samples should be collected.